2020
DOI: 10.26656/fr.2017.4(3).390
|View full text |Cite
|
Sign up to set email alerts
|

Orange-fleshed sweet potato grown in Viet Nam as a potential source for making noodles

Abstract: Orange-fleshed sweet potato (OFSP) noodles were created by replacing a portion of the wheat flour with OFSP flour in a formulation. This study was performed to identify the physical and chemical characteristics as well as sensorial attributes of noodles prepared from OFSP with some flours (wheat flour and semolina). The addition of xanthan gum and incubation time was examined. Instrumental analyses of noodles (cooking loss, volume increase, rehydration ratio, structure and microstructure) were carried out to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…The control sample was formulated with whole wheat flour, while the other formulations had high resistant starch flours of 22.5% of the total components of the noodles in F1, 30% in F2, and 37.5% in F3. The process of making the noodles was carried out according to Thuy et al (2020). The prepared noodles were dried in an oven at 65 o C until the moisture content of the dried sample was around 6-7%, and was ground before measurement of the RS content.…”
Section: Preparation Of Noodlesmentioning
confidence: 99%
“…The control sample was formulated with whole wheat flour, while the other formulations had high resistant starch flours of 22.5% of the total components of the noodles in F1, 30% in F2, and 37.5% in F3. The process of making the noodles was carried out according to Thuy et al (2020). The prepared noodles were dried in an oven at 65 o C until the moisture content of the dried sample was around 6-7%, and was ground before measurement of the RS content.…”
Section: Preparation Of Noodlesmentioning
confidence: 99%
“…1[k, l, m]) had obvious filamentous areas that suggest the development of starch-protein network (Menon et al, 2012). Thuy et al (2020) reported that the SEM results were able to discover the number of alveoli inside the swelled starch granules and the shape of protein network inside the cooked noodles. Our SEM results showed that the addition of SPF improved the starchprotein matrix in SC2, SC3 and SC4 formulas as gluten-free noodles.…”
Section: Scanning Electronic Microscopymentioning
confidence: 99%
“…noodles (gluten‐free) are better in texture than mung bean starch noodles (Chen et al, 2002); and the hot extrusion to sweet potato starch enhances water absorption index, cooking time and sensory acceptability (Adedotun et al, 2015). Also, the effects of adding sweet potato flour/starch to wheat noodles led to an increase in softness, extensibility and colour acceptability; as well as ash, crude fibre and resistant starch (RS) content; with a decrease in rapidly digestible starch (RDS) content (Menon et al, 2012; Taneya et al, 2014; Thuy et al, 2020). Also, it was reported that sweet potato could help in preventing or reducing the risks of developing diabetes and cancer (ILSI, 2008; Mohanraj & Sivasankar, 2014), thus, raising its potential as a main ingredient in developing gluten‐free noodles with better physiochemical and the nutritional properties.…”
Section: Introductionmentioning
confidence: 99%
“…The sweet potatoes were washed with tap water to remove soil, peeled and sliced into thin sheets, and then blanched for two minutes in 100°C water before drying in an oven at 65°C for 7 hours until the moisture content of the dried sample was around 6%-7% [7]. Green bananas were peeled and immediately placed in a sodium sulfite (Na 2 SO 3 ) solution with a concentration of 500 ppm and left to soak for 30 minutes to prevent polyphenol oxidation from polymerizing the natural occurring polyphenols in the banana skin.…”
Section: Preparation Of Samplesmentioning
confidence: 99%